2021
DOI: 10.1002/onco.13870
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Impact of KRAS G12C Mutation in Patients with Metastatic Colorectal Cancer: A Multicenter Retrospective Observational Study

Abstract: Background. KRAS is one of the most frequently mutated oncogenes in colorectal cancer (CRC). Recently, a novel therapy targeting KRAS G12C mutation has demonstrated promising activities for corresponding advanced solid tumors, including metastatic CRC (mCRC). However, the prognostic impact of the KRAS G12C mutation remains unclear in patients with mCRC. Materials and Methods. We retrospectively reviewed medical records of patients with mCRC who received first-line chemotherapy between January 2005 and December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 26 publications
(38 reference statements)
10
24
1
Order By: Relevance
“…), and they did not also report which kind of palliative chemotherapy regimen those patients had received, thus preventing any other comparison with our study. Recently, Chida et al (21) have also reported that KRAS G12C mutation might be associated with worse prognosis in patients affected by mCRC treated with first-line chemotherapy. It must be noticed, however, that the authors have enrolled a rather heterogenous group of patients, treated with different chemotherapy combinations (monotherapy, doublets, and triplets), and there was a significant proportion of patients who did not receive first-line treatment with Bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
“…), and they did not also report which kind of palliative chemotherapy regimen those patients had received, thus preventing any other comparison with our study. Recently, Chida et al (21) have also reported that KRAS G12C mutation might be associated with worse prognosis in patients affected by mCRC treated with first-line chemotherapy. It must be noticed, however, that the authors have enrolled a rather heterogenous group of patients, treated with different chemotherapy combinations (monotherapy, doublets, and triplets), and there was a significant proportion of patients who did not receive first-line treatment with Bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of different KRAS mutations on the clinical behavior of metastatic CRC (mCRC) has been explored, and differences have been reported (9). The clinical relevance of KRAS-G12C is unclear (10)(11)(12)(13)(14)(15)(16)(17). The frequency of KRAS-G12C has been reported to be 2%-8% in large databases of molecularly analyzed CRCs (12,14,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of KRAS-G12C has been reported to be 2%-8% in large databases of molecularly analyzed CRCs (12,14,18,19). In hospital-based series, the proportion of KRAS-G12C tumors was 2%-4% of all mCRC tumors (11,15,16,20), whereas greater variability was seen in the proportion of the KRAS-mutated population (6%-17%) (11,13,16,17,(20)(21)(22). Sex-and age-related differences and differences in the metastatic pattern have been reported between different KRAS mutations, with no consistent results (12,13,22).…”
Section: Introductionmentioning
confidence: 99%
“…The multicenter and retrospective analysis revealed that the EPIMMUNE signature could predict the response to anti-PD-1 treatment in non-small-cell lung cancer ( Seremet et al, 2016 ). In metastatic melanoma treated with CTLA-4 blockers, responders and non-responders to ICI had a differential DNA methylation pattern ( Chida et al, 2021 ). To better understand the individual heterogeneity of TME-meditated 5mC modification patterns, the 5mCscore was established to assess the 5mC modification pattern of individuals with LUAD.…”
Section: Discussionmentioning
confidence: 99%